Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s00248-017-0973-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Anaerobic Hydrocarbon-Degrading Bacteria in Soils from King George Island, Maritime Antarctica

Abstract: Anaerobic diesel fuel Arctic (DFA) degradation has already been demonstrated in Antarctic soils. However, studies comparing the distribution of anaerobic bacterial groups and of anaerobic hydrocarbon-degrading bacteria in Antarctic soils containing different concentrations of DFA are scarce. In this study, functional genes were used to study the diversity and distribution of anaerobic hydrocarbon-degrading bacteria (bamA, assA, and bssA) and of sulfate-reducing bacteria (SRB-apsR) in highly, intermediate, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The current study demonstrated that the microbial community was detected through the oil-contaminated and non-oil-contaminated soils, where their numbers were observed in the stations at levels of log 5.3 -6.4 CFU g -1 . Several prior publications have investigated the microbial community in the different areas of oil-contaminated and nonoil-contaminated soils by means of both conventional and molecular methods [14,15,16]. In agreement with the current results, data obtained from the study of Wolińska et al ., showed that the numbers of cultivable bacteria which could be isolated from contaminated and control samples were different but no significant differences were found [14].…”
Section: Counting Of Bacteriasupporting
confidence: 90%
“…The current study demonstrated that the microbial community was detected through the oil-contaminated and non-oil-contaminated soils, where their numbers were observed in the stations at levels of log 5.3 -6.4 CFU g -1 . Several prior publications have investigated the microbial community in the different areas of oil-contaminated and nonoil-contaminated soils by means of both conventional and molecular methods [14,15,16]. In agreement with the current results, data obtained from the study of Wolińska et al ., showed that the numbers of cultivable bacteria which could be isolated from contaminated and control samples were different but no significant differences were found [14].…”
Section: Counting Of Bacteriasupporting
confidence: 90%
“…While the nitrate produced could potentially be converted to ammonium through assimilatory nitrate reduction, we instead found genetic evidence for its use as an electron acceptor for anaerobic respiration through denitrification, which would result in loss of N from the system (Figure 5b). The potential role of denitrifiers in the degradation of aromatic hydrocarbons in Antarctic soils has also been proposed by Sampaio et al (2017).…”
Section: Metagenomic Functional Analysis Of Microbial Communitymentioning
confidence: 99%
“…Along with type-II Methylocystis, the type-I methanotroph Methylococcus (3.2%) and unclassified Methylococcaceae (6.5%) were also detected in the bioreactor, suggesting their potential roles for methane oxidation . In addition to aerobic methanotrophs, two recognized denitrifying bacteria Acidovorax and Lautropia were detected, accounting for 4.1 and 2.9% of the total microbial sequences, respectively. Additionally, unclassified members of Rhodocyclaceae were also enriched, with relative abundance increasing from 0.1% in the inoculum to 5.7% on day 360.…”
Section: Resultsmentioning
confidence: 99%